Transforming safety for the future: Introducing cutting-edge aerodynamic endonasal filtration innovation in a post-pandemic era - Broccolo, Francesco; D’Urso, Fabiana; Imperi, Enrico; Picano, Alfredo (International journal of health sciences, 2024)
Is there a solution missing for personal respiratory protection that is user-friendly, suitable for everyday use, and offers low visual and physical intrusion while safeguarding against a broad spectrum of threats, including airborne pathogens, specifically fine and ultrafine particles? Reflecting on recent challenges, during the SARS-CoV-2 pandemic, occupational safety devices like filtering face masks were repurposed for the general population. However, these devices, designed for controlled work environments, revealed limitations when used extensively in daily life, including issues with comfort, compliance, and compatibility with various activities. This necessitates a shift in perspective, emphasizing overall daily life effectiveness over isolated efficacy. Nasal filters emerge as potential solutions, yet their systematic definition as devices and products is lacking, underestimating the complexity required for optimal performance. This paper draws insights from the pandemic experience to propose systematic product specifications and characterization methods for an innovative respiratory protection device, addressing the limitations associated with endonasal applications and advocating for technological advancements.